I-PfoP3I: A Novel Nicking HNH Homing Endonuclease Encoded in the Group I Intron of the DNA Polymerase Gene in Phormidium foveolarum Phage Pf-WMP3 - Kong, Shuanglei (Public Library of Science, 2012)
Homing endonucleases encoded in a group I self-splicing intron in a protein-coding gene in cyanophage genomes have not been reported, apart from some free-standing homing edonucleases. In this study, a nicking DNA endonuclease, I-PfoP3I, encoded in a group IA2 intron in the DNA polymerase gene of a T7-like cyanophage Pf-WMP3, which infects the freshwater cyanobacterium Phormidium foveolarum is described. The Pf-WMP3 intron splices efficiently in vivo and self-splices in vitro simultaneously during transcription. I-PfoP3I belongs to the HNH family with an unconventional C-terminal HNH motif. I-PfoP3I nicks the intron-minus Pf-WMP3 DNA polymerase gene more efficiently than the Pf-WMP4 DNA polymerase gene that lacks any intervening sequence in vitro, indicating the variable capacity of I-PfoP3I. I-PfoP3I cleaves 4 nt upstream of the intron insertion site on the coding strand of EXON 1 on both intron-minus Pf-WMP3 and Pf-WMP4 DNA polymerase genes. Using an in vitro cleavage assay and scanning deletion mutants of the intronless target site, the minimal recognition site was determined to be a 14 bp region downstream of the cut site. I-PfoP3I requires Mg(2+), Ca(2+) or Mn(2+) for nicking activity. Phylogenetic analysis suggests that the intron and homing endonuclease gene elements might be inserted in Pf-WMP3 genome individually after differentiation from Pf-WMP4. To our knowledge, this is the first report of the presence of a group I self-splicing intron encoding a functional homing endonuclease in a protein-coding gene in a cyanophage genome.